The Effectiveness of Training in Communicative Skills Training with A Cognitive - Behaviorist Approach on Spouses 'Marital Adjustment and the Prevention of Addicts from Relapsing in Male Addicts in Isfahan (Drug Control Headquarters, Research and Education Office, 2008)
Objectives: The general objective of the present research is to examine the effect of training in communicative skills with a cognitive - behaviorist approach on spouses 'marital adjustment and the prevention of men's addiction from relapsing. Methods: This study is a Quasi - experimental research which is carried on with 2 groups of control and experimental subjects by using an experimental variable (training in relation ship skills for 8 sessions), in this study we have also used a pretest and a post test and follow up was used after 2 months. The samples were selected among addicts 'wives. The addicts were completing their quitting stages and they had been referring to addiction quitting center in Isfahan for four month And the Wives marital adjustment scores were below average (1 Standard deviation below average). The study tool was marital adjustment measure of Spanier (1979) with 4 factors including marital satisfaction .mutual correlation, mutual agreement and love expression. To measure the possibility addicts 'relapsing to drug, experimental test for fast recognition (Rapid) was utilized. The selection of samples was done through available sampling and for analysis of data repeated measures of variance analysis and χ2 statistical test were used in this study. Findings: The result showed that training in communicative skills with a cognitive-behaviorist approach influences positively general adjustment. No positive effect was noticed in marital satisfaction and mutual correlation factors. There is positive effect of training skills on mutual agreement and love expression factors. Furthermore, the prevention of addicts from relapsing in male addicts, the number of relapse in control group is more than experimental group but this different was not significant. Results: In general, communicative skills training with a cognitive - behaviorist approach effects spouses adjustment of male addicts.